Effect of Individual Shrink Wrapping on Spoilage and Quality of Peaches during Storage - Singh, Dinesh; Mandal, Gautam; Sharma, R R (Journal of Agricultural Engineering, 2009)
Effect of individual heat shrink wrapping of peaches (Prunus persica (L.) Batsch.) were studied using heat shrinkable 50 Âµ LDPE and 20 Âµ LLDPE film to enhance the shelf life in cool chamber (5 ± 1degree C, 90 â€“ 95% RH). The minimum physiological loss in weight (PLW) was 0.65% in 50Âµ LDPE and 0.7% in 20Âµ LLDPE. The PLW drastically reduced as compared to control (45.26%) after 42 days of storage. The spoilage of fruits was 7% in 20Âµ LLDPE wrapped fruits. No fruit decay was found in unwrapped samples, but all the fruits shrivelled after 14 days of storage. The firmness of the fruits was better in 20Âµ LLDPE as compared to control. The colour of the fruits changed from greenish-yellow to yellowishâ€“red, with corresponding rise of a, b and Yi value, and decreased L value. The total soluble solids increased and the titrable acidity decreased in all the treatments during storage. It may be concluded that the shelf life of the fruits in cool chamber may be extended up to 42 days by individual heat shrink wrapping with 20Âµ LLDPE film after post harvest treatment with carbendazim (500 ppm).